Предмет: Алгебра,
автор: Kubik5Rubik
помогите пожалуйста срочно!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Приложения:
Ответы
Автор ответа:
1
х=а,⇒ 2х+3у=3х⇒х=3у и
по условию х+6у=9⇒х=9-6у
получаем систему х=3у,
х=9-6у ⇒ 3у=9-6у, 9у=9, у=1,
значит х=3у=3
Ответ А
по условию х+6у=9⇒х=9-6у
получаем систему х=3у,
х=9-6у ⇒ 3у=9-6у, 9у=9, у=1,
значит х=3у=3
Ответ А
Похожие вопросы
Предмет: Русский язык,
автор: savoksan
Предмет: Русский язык,
автор: Fedan1
Предмет: Русский язык,
автор: davidworsont
Предмет: Математика,
автор: Igor228youtube
Предмет: Математика,
автор: liza3634